Persepsi Guru Pamong terhadap Praktik Mengajar Mahasiswa Program Pengalaman Lapangan (PPL) - Wahyuningrum, Dila Indah; Tinambunan, Jamilin (UIR PRESS, 2021)
This research is motivated by PPL student teaching practice which is an activity that must be carried out by FKIP UIR student which includes teaching training activities and other educational tasks in school. This study aims to describe, analyze, and interpret the perception of teachers pamong to the teaching practice of PPL students of Riau Islamic University at SMA YLPI Pekanbaru school Year 2019/2020 in the activities of opening lessons, explaining lesson materials, managing class activities, and closing lessons. The method used in this study is descriptive method, the approach used is to use qualitative approach, while the data collection teachnique used is to use the spread of questionnaires. In analyzing the author’s data using several relevant theories, namely Slameto (2003), Asril (2015), Djamarah (2005), Jalaluddin (2011) and Alma (2014). The samples in this study used a full sample or a total sample, or the entire population was determined to be a sample of 23 PPL student at SMA YLPI Pekanbaru school year 2019/2020. The results of this study concluded that the perception of teachers pamong to the teaching practice of PPL students in the activities of opening lessons in good category with percentage (79,71%), activities explaining lesson materials categorized fairly by percentage (67,39%), activities managing good categorized classes with percentages (80,63%), and activities closing lessons in goof category with percentage (81,88%). So, teacher pamong’s perception of teaching practices of PPL students of Riau Islamic University at SMA YLPI Pekanbaru school year 2019/2020 is well categorized (77,4%).